ACR management guidelines for the treatment of gout: What’s new and what’s controversial - M. S. Eliseev (Научно-практическая ревматология)
The community of many national and international recommendations dedicated to the treatment of a specific disease, including gout, is fully justified, since it allows taking into account, for example, regional, ethnic characteristics of the manifestations of the disease, which can be important when choosing a therapy. However, this is often associated with dissonance regarding the solution of key issues facing the practitioner. The publication in 2020 of the updated American College of Rheumatology (ACR) guidelines for the management of gout revealed controversy with some of the previous version’s postulates, as well as with other similar work, for example, with the guidelines published in the same year and the French Association of Rheumatology. Among the controversial provisions of the new version of the ACR recommendations are the unified target level of uric acid for all patients, indications for drug therapy, the choice of a drug in patients with reduced renal function, prevention of arthritis attacks when starting uratelowering therapy. This article discusses these and other controversial issues in gout therapy based on an analysis of the latest ACR guidelines.